USO DE SERIES SINTÉTICAS DE CAUDALES MENSUALES EN EL CÁLCULO DEL COSTO MARGINAL DE ENERGÍA DEL SISTEMA ELÉCTRICO INTERCONECTADO NACIONAL DEL PERÚ - Sarango J., Douglas (2009)
In this research it was determined the feasibility of using synthetic series of monthly average flow for the determination of the average marginal cost of energy in the National Interconnected Electric System of Peru – SEIN, taking as a case study of implementing bar tariff setting in 2004, where it was used the PERSEO model for planning, simulation and optimization of the hydrothermal system in Peru. The model is currently used by the Deputy Manager of tariff regulation (GART) of the Agency for Supervision of Investment in Energy and Mining - OSINERGMIN. The model use as hydrological information the average monthly flow series of tributaries to the historical attractions of the 23 river basins of the SEIN, one of the main is the basin of the Junin Lake, whose water is used by the Mantaro and Restitution hydroelectric, generating almost 20% of the power of our country. With the HEC-4 program, developed by the Hydrological Engineering Center of the USA, from the time series of monthly historical flows tributary to the Junin Lake, 50 series were generated synthetic monthly flow, determined from them a dry series, a average series and a wet series, information that was used in the PERSEO model to calculate the average marginal cost of energy of SEIN for each case. The results obtained from the average marginal cost of energy with the use of synthetic series of monthly flows, for the dry case, average case and wet case, with the PERSEO model, compared to the historical event, are lower in order of 1.14, 1.55 and 0.87 US $/MWh, the results will determine a decline in energy prices for end users, such as the domestic, commercial, industrial and mining users.